Microstructure and mechanical properties of double-side friction stir welded 6082Al ultra-thick plates. (15th March 2020) - Yang, C.; Zhang, J.F.; Ma, G.N.; Wu, L.H.; Zhang, X.M.; He, G.Z.; Xue, P.; Ni, D.R.; Xiao, B.L.; Wang, K.S.; Ma, Z.Y.
Abstract: In the present work, 80 mm thick 6082Al alloy plates were successfully double-side welded by friction stir welding (FSW). The relationship between the microstructures and mechanical properties was built for the double-side FSW butt joint with more attention paid to the local characteristic zones. It was shown that a phenomenon of microstructural inhomogeneity existed in the nugget zone (NZ) through the thickness direction. The grain size presented an obvious gradient distribution from the top to the bottom for each single-pass weld, and the microhardness values decreased from both surfaces to the middle of the NZ. The lowest hardness zone (LHZ) exhibited a "hyperbolical"-shaped distribution extending to the middle of the NZ. Similar tensile properties were obtained in the three sliced specimens of the FSW joint, and the joint coefficient reached about 70% which achieved the same level as the conventional FSW Al alloy joints. Finite element modeling proved that the "hyperbolical"-shaped heat affected zone (HAZ) was beneficial to resisting the strain concentration in the middle layer specimen which helped to increase the tensile strength. Based on the analysis of the hardness contour map, tensile property and microstructural evolution of the joints, an Isothermal Softening Layer (ISL) model was proposed and established, which may have a helpful guidance for the optimization on the FSW of ultra-thick Al alloy plates.